It Is Necessary to Purpose an Add-on to the American Classification of Endometriosis? This Disease Can Be Compared to a Malignant Proliferation While Remaining Benign in Most Cases. EndoGram® Is a New Profile Witness of Its Evolutionary Potential - Bouquet de Joliniere, Jean; Major, Attila; Ayoubi, Jean Marc; Cabry, Rosalie; Khomsi, Fathi; Lesec, Guy; Frydman, René; Feki, Anis (Frontiers in Surgery, 2019)
Endometriosis is a curious pathology that has been the source of many international publications. Its etiology remains mysterious but seems to have multiple causes. It is a complex disease whose lesions are very heterogeneous on the part of their location (deep endometriosis, superficial, ovarian cyst), extent, associated symptoms, evolution or aggressiveness of the disease, and response to treatments. Furthermore, it evolves in pushes, remains autonomous, and is responsible for superficial and deep lesions that explain its two challenges: pain and infertility. It has always been classified by the size of its anatomical lesions—Acosta classification (17), revised by the American fertility society (AFS) (22), and the American society of reproductive medicine (ASRM) classification with a description of the disease at different stages: minimal (score of 1 to 5), mild (6-15), moderate (16 to 40), and severe (>40) (21). If this classification provides a complete repertoire of implants (anatomic) (13), the attribution of points is arbitrary. In fact, the size of the lesions is not synonymous with the difficulty to treat them surgically. Their location, if deep, is larger than the size of ovarian endometriomas. In addition, small anatomical but evaluative lesions will have more impact than big fibrous and stable lesions (Picture 1). Thus, attempts to explain their inflammatory side effect have been proposed (1, 23). The French classification (nodule, ovaries, adhesions, tube and inflammation (FOATI) (13) has had the merit of taking the phenomenon into account. In our opinion, we must go much further and propose an amendment in this classification, taking into account the evolution of the lesions and their deep molecular biology because in reality, the lesions are not at the same stage.